Storage Behaviour of Simarouba Seed, Oil and Cake - Ramesh Babu, C.; Raghun, P.; Jayaveera, K.N. (Asian Journal of Chemistry, 2010)
Simarouba glauca seed stored over a year under normal conditions did not undergo spoilage. The stability order of crude Simarouba oil, bleached oil and refined Simarouba oil towards hydrolytic and oxidative rancidities follows the order crude Simarouba oil > bleached oil > refined Simarouba oil. Expeller Simarouba cake developed high FFA after a few months of storage.